2023
DOI: 10.1108/cdi-05-2023-0154
|View full text |Cite
|
Sign up to set email alerts
|

Self-goal setting as a way to career sustainability: exploring the roles of career crafting and perceived organizational goal clarity

Xiaolin Ge,
Haibo Yu,
Qing Zhang
et al.

Abstract: PurposeAs an increasingly important variable in the career field, career sustainability has received particular attention, yet few empirical studies have been conducted to examine its antecedents. The authors propose a moderated mediation model based on the goal-setting theory and the wise proactivity perspective for exploring when and how self-goal setting can influence career sustainability.Design/methodology/approachThe authors use a time-lagged design and collect three waves of data from 1,260 teachers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Recent research by many scholars has focused on understanding and promoting the continuous development of individuals in their careers [11,[29][30][31][32]. By synthesizing different studies, they reveal the main research trends and theoretical advancements in sustainable employment.…”
Section: Data Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research by many scholars has focused on understanding and promoting the continuous development of individuals in their careers [11,[29][30][31][32]. By synthesizing different studies, they reveal the main research trends and theoretical advancements in sustainable employment.…”
Section: Data Resultsmentioning
confidence: 99%
“…Their research indicated the importance of leadership styles in digital transformation for employee adaptability and career development. Ge et al [29] revealed how individual career development practices and organizational support can collectively promote sustained career development by exploring the impact of self-goal se ing on career sustainability, the role of career shaping, and organizational goal clarity in addressing the sustainability of specific groups. Luo et al [30] provided insights into how female workers in the e-commerce industry can enhance their self-efficacy and career sustainability through supportive supervisor behavior that accommodates family needs.…”
Section: Data Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third cluster assessed career sustainability in a variety of other ways that do not correspond to the first two categories. Three of these studies (Fang et al, 2021;Ge et al, 2023;Nakra & Kashyap, 2023) used a composite measure of career sustainability developed by Chin et al (2021) that assessed the extent to which a career is flexible, renewable, integrative, and resourceful. A number of studies measured other positive characteristics or qualities to assess career sustainability, such as reflexivity, self-awareness, and a clear vision for the future (Argyropoulou et al, 2020), career growth (Lu et al, 2019), career attainment or advancement (Bhaskar et al, 2022;Dlouhy & Froidevaux, 2024;Herman & Lewis, 2012), work ability (Stuer et al, 2019), and career control (Xu et al, 2020).…”
Section: The Measurement Of Career Sustainabilitymentioning
confidence: 99%
“…Given that careers are affected by different life domains, adopting a perspective incorporating work and family contextual determinants and the harmony between these contexts can have the potential to broaden our understanding of sustainable careers [9]. Moreover, along with the contextual determinants, the recent literature has provided evidence for the individual determinants of sustainable careers, such as personality traits, career competencies, or individual strategies [11][12][13][14]. Although these studies have provided valuable insights into sustainable careers, there remains a notable lack of evidence on the role of individual career proactivity.…”
Section: Introductionmentioning
confidence: 99%